Root‐knot nematodes induce gall formation by recruiting developmental pathways of post‐embryonic organogenesis and regeneration to promote transient pluripotency. Issue 1 (15th April 2020) - Olmo, Rocío; Cabrera, Javier; Díaz‐Manzano, Fernando E.; Ruiz‐Ferrer, Virginia; Barcala, Marta; Ishida, Takashi; García, Alejandra; Andrés, María Fe; Ruiz‐Lara, Simón; Verdugo, Isabel; Pernas, Mónica; Fukaki, Hidehiro; et al.
Summary: Root‐knot nematodes (RKNs; Meloidogyne spp.) induce new post‐embryogenic organs within the roots (galls) where they stablish and differentiate nematode feeding cells, giant cells (GCs). The developmental programmes and functional genes involved remain poorly defined. Arabidopsis root apical meristem (RAM), lateral root (LR) and callus marker lines, SHORT‐ROOT/SHR, SCARECROW/SCR, SCHIZORIZA/SCZ, WUSCHEL‐RELATED‐HOMEOBOX‐5/WOX5, AUXIN‐RESPONSIVE‐FACTOR‐5/ARF5, ARABIDOPSIS‐HISTIDINE PHOSPHOTRANSFER‐PROTEIN‐6/AHP6, GATA‐TRANSCRIPTION FACTOR‐23/GATA23 and S‐PHASE‐KINASE‐ASSOCIATED‐PROTEIN2B/SKP2B, were analysed for nematode‐dependent expression. Their corresponding loss‐of‐function lines, including those for LR upstream regulators, SOLITARY ROOT/SLR/IAA14, BONDELOS/BDL/IAA12 and INDOLE‐3‐ACETIC‐ACID‐INDUCIBLE‐28/IAA28, were tested for RKN resistance/tolerance. LR genes, for example ARF5 (key factor for root stem‐cell niche regeneration), GATA23 (which specifies pluripotent founder cells) and AHP6 (cytokinin‐signalling‐inhibitor regulating pericycle cell‐divisions orientation), show a crucial function during gall formation. RKNs do not compromise the number of founder cells or LR primordia but locally induce gall formation possibly by tuning the auxin/cytokinin balance in which AHP6 might be necessary. Key RAM marker genes were induced and functional in galls. Therefore, the activation of plant developmental programmes promoting transient‐pluripotency/stemness leads to the generation of quiescent‐centre and meristematic‐like cell identities within the vascular cylinder of galls. Nematodes enlist developmental pathways of new organogenesis and/or root regeneration in the vascular cells of galls. This should determine meristematic cell identities with sufficient transient pluripotency for gall organogenesis.